Effect of Incorporation of Cellulose Industrial Residue in Concrete Matrix - Mbadike, Elvis M; F.O, Okafor; J.C, Agunwamba (International Journal of Chemical and Process Engineering Research, 2016)
The goal of producing concrete that provides long term durability with regard to properties such as strength and reduced susceptibility to alkali-silica reactions has led to the development of several high performance materials. In this research work, the effect of cellulose industrial residue in concrete matrix was investigated. A mix proportion of 1:1:6:3.2 with water-cement ratio of 0.47 were used. The percentage replacement of Ordinary Portland Cement (OPC) with cellulose industrial residue (CIR) is 0%, 5%, 10%, 20%, 30% and 40%. Concrete cubes of 150mm x 150mm x 150mm of OPC/CIR were cast and cured at 3,7,28,60 and 90 days respectively. At the end of each hydration period, the three concrete cubes for each hydration period were crushed and their average compressive strength recorded. A total of ninety (90) concrete cubes was cast. The result of the compressive strength test for 5-40% replacement of cement with cellulose industrial residue ranges from 13.02-32.81 N/mm2 as against 25.60-42.08 for the controi test. Similarly, the setting time of 5-40% replacement of cement with CIR ranges from 61-118mins for the initial setting time and 620-836mins for the final setting time as against 52mins and 950mins for the initial and final setting time respectively for the control test (0% replacement). The result of the slump test for 5-40% replacement of cement with CIR ranges from 12-53mm as against 6mm for the control test. The major aim of this research work is to determine the effect of cellulose industrial residue when used at a certain replacement level of cement in concrete matrix.